2022
DOI: 10.3390/jcm11041025
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma of the Vulva: A Survival and Epidemiologic Study with Focus on Surgery and Radiotherapy

Abstract: Vulvar squamous cell carcinoma (SCC) is the most frequent vulvar neoplasia. While the primary role of surgery is widely accepted, large population studies are needed to compare survival between diverse treatment modalities and to identify independent prognostic factors to help council patients and guide oncological treatment. The U.S. National Cancer Index, Surveillance, Epidemiology and End Results (SEER) program data between 2000 and 2018 was screened for all squamous cell carcinoma affecting the vulva. Raw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
6
5
1
Order By: Relevance
“…We also observed that chemotherapy was associated with improved OS, which was concordant with Mao Y et al [14] and Vulcan et al [23]. However, Scampa et al [16] contrastingly observed that chemotherapy was not associated with OS benefits, possibly because it was mostly prescribed in patients with advanced diseases, thereby demonstrating lower survival rates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also observed that chemotherapy was associated with improved OS, which was concordant with Mao Y et al [14] and Vulcan et al [23]. However, Scampa et al [16] contrastingly observed that chemotherapy was not associated with OS benefits, possibly because it was mostly prescribed in patients with advanced diseases, thereby demonstrating lower survival rates.…”
Section: Discussionsupporting
confidence: 88%
“…Nomogram is a widely used graphical scoring model that combines various independent risk factors to predict the overall survival of cancer patients [10,11]. Presently, there are limited studies on nomograms for vulvar cancer [12][13][14][15][16] and none for elderly vulvar cancer patients. Considering that these patients are at high risk of developing complications and mortality, it is very important to identify prognostic factors that could affect their prognosis, accurately estimate their overall survival and develop individualized treatments that could improve their outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding chemotherapy, our results are consistent with the idea that it can significantly improve OS in vulvar cancer patients [31]. However, a study by Scampa et al [32] reported that the OS of patients benefiting from chemotherapy was statistically lower than those who did not benefit, possibly because chemotherapy is primarily administered to patients with advanced diseases, leading to shorter survival time.…”
Section: Findings In Relation To Published Literaturesupporting
confidence: 89%
“…VSCC. Specifically, older patients exhibited poorer survival rates, consistent with prior research [16,19,27,28]. Our study also confirms that both TNM and AJCC stages are significant predictors for OS and cancer-specific CSS in VSCC patients, aligning with their established roles in predicting patient survival [15].…”
Section: Findings In Relation To Published Literaturesupporting
confidence: 89%
See 1 more Smart Citation